Effect of analgesia plus placebo on low back pain – a systematic review and meta-analysis - Safari, Mirbahram; Shojaee, Pouyan; Shokohi, Shahram; Shojaee, Shayan; Banei, Vahid (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2025)
In the present study, the effect of analgesia plus placebo on low back pain was investigated. The researchers of the current study searched for key words associated with its goals in the international databases Scopus, Cochrane, Embase, and MEDLINE (PubMed) for January 2014 – December 2024 using 95% CI effect size using inverse-variance techniques and a fixed-effects model. Stata was used for the meta-analysis (version 17). The meta-analysis showed that use of medication plus placebo can reduce low back pain by 84% [ES 0.84 (–0.25, 1.92), I2 = 0%]. In conclusion, when compared to medication plus placebo, adding Diclofenac, Tramadol, Tizanidine, Aceclofenac, Thiocolchicoside, Naproxen, Metaxalone, Baclofen, and Ibuprofen does not improve functioning or pain for acute low back pain.